Nicaragua : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This paper provides the details of the IMF's projections and estimates on Nicaragua's gross domestic product by expenditure; value added in agriculture and manufacturing; central government operations; operations of the rest of the general government and public utility enterprises; summary balance of payments; trade account indicators; public sector external debt and debt service; summary accounts of the central bank and the financial system; consumer price index; resource balance and financing of investment, and so on. It also provides the statistical appendix report on real, fiscal, monetary, and external sectors.